1979
DOI: 10.1002/ijc.2910240111
|View full text |Cite
|
Sign up to set email alerts
|

Selective cytotoxicity of tunicamycin for transformed cells

Abstract: W e have studied the effects of tunicamycin, an inhibitor of dolichol pyrophosphate-dependent glycosylation of proteins, on the viability of transformed and non-transformed fibroblasts i n culture. W e have shown that a low concentration of tunicamycin (0.05 pg/ml o r 5 x M) is cytotoxic toward a variety of transformed cell lines, including virally o r chemically transformed fibroblasts from chick embryo, r a t kidney, human lung, and mouse. The corresponding non-transformed cell lines were resistant t o the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 32 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Duskin and Bornstein [50] found that tunicamycin was toxic to virally transformed mouse 3T3 and human WI-38 cells but not to the corresponding untransformed cell lines. Olden et a1 [51] confirmed this observation on a variety of fibroblast cell lines and also found that permanent transformed cell lines were resistant to tunicamycin treatment. However, even cells in which tunicamycin was not toxic showed reductions in their CR.429…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Duskin and Bornstein [50] found that tunicamycin was toxic to virally transformed mouse 3T3 and human WI-38 cells but not to the corresponding untransformed cell lines. Olden et a1 [51] confirmed this observation on a variety of fibroblast cell lines and also found that permanent transformed cell lines were resistant to tunicamycin treatment. However, even cells in which tunicamycin was not toxic showed reductions in their CR.429…”
Section: Discussionmentioning
confidence: 72%
“…Cell surface glycosaminoglycans are the other candidates for tunicamycin modification, because Satoh et a1 [58] demonstrated that B16 melanoma cells produce hyalurounic acid, chondroitin sulfate, and heparan sulfate. In addition, proteoglycan synthesis in chick embryo fibroblasts and embryonic chick cornea were inhibited by tunicamycin [51,591, and proteoglycans appear to be involved in cell adhesion to substratum [60, 611. bohydrates are important in the B16 melanoma metastatic process are consistent with previous reports [ 1 1, 14, 621. Elsewhere we have described the effects of tunicamycin on B 16-F1 and B 16-F10 cellular metabolism and glycoproteins synthesis in relation to the blood-borne arrest and lung colonization potentials [24].…”
Section: Irimura and Nicolsonmentioning
confidence: 99%
“…This effect has been correlated with the presence of certain surface sialoglycoproteins (8,9,11). However, since tunicamycin is known to be toxic at least for most tumor cells (12,13), the significance of this finding remains unclear.…”
mentioning
confidence: 99%
“…The function of carbohydrate components of glycoproteins can be conveniently studied in cultured cells by the use of tunicamycin (TM), an antibiotic that specifically inhibits protein glycosylation (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Treatment of cells with TM results in the synthesis of glycoproteins deficient in asparagine-linked oligosaccharides (6,18,19).…”
mentioning
confidence: 99%